The potency of chicken egg yolk immunoglobulin (IgY) specific as immunotherapy to Mycobacterium tuberculosis infection - Sri Agus Sudjarwo; Koerniasari Eraiko; Giftania Wardani Sudjarwo; Koerniasari (Wolters Kluwer Medknow Publications, 2017)
The aim of this study was to characterize of chicken egg yolk immunoglobulins (IgYs) specific as immunotherapy to Mycobacterium tuberculosis complex (MTBC) infection. Lohmann laying hens were immunized intramuscularly with antigenic of MTBC. Egg yolk was separated from egg white, and IgY antibody was then purified by multiple polyethylene glycols 6000 extraction and ammonium sulfate purification steps. The IgY anti-MTBC concentration in egg yolk increased at 2 weeks and it reached a maximum at 4 weeks after immunization. After 6 weeks, the levels of IgY anti-MTBC decreased gradually. The antibody of MTBC was detected and produces a specific line of precipitation in agar gel precipitation test beginning the week 2 after the first immunization. Analysis of results obtained with ELISA showed a significant increase in the MTBC specific antibodies after 2 weeks and reached a plateau at 4 weeks from the booster immunization. Sodium dodecyl sulfate-polyacrylamide gel electrophoresis revealed the IgY preparation to be pure and dissociated into protein bands with molecular weights of 112, 78, 69, 49, and 28 kDa and Western blot analysis shown the presence of anti-MTBC IgY in egg yolks, with molecular weights of approximately 78 kDa. These results suggested that egg yolk could be a practical strategy in large-scale production of specific anti-MTBC IgY for immunotherapy of TBC.